Assessment of Vernacular Housing in the Dominican Republic Using Simulations - Letzai Ruiz-Valero; Virginia Flores-Sasso; Esteban Prieto-Vicioso; Gabriela Fernández-Flores (Buildings)
Dominican vernacular architecture, based on the Spanish-influenced indigenous bohio, is built with natural materials. This housing model has remained practically unchanged for five centuries, responding adequately to the tropical Caribbean climate. However, it is necessary to characterize this behavior to verify the indoor comfort conditions of this housing typology. The aim of this research is to evaluate the behavior of a vernacular house located in Villa Sombrero, Peravia Province, Dominican Republic, using a simulation model. For this purpose, a bohio was selected, which has a simple rectangular volume. Simulations were carried out using Design Builder software, considering the passive strategies incorporated in the bohio. The results indicate that indoor ambient temperature remains within the comfort range throughout the annual cycle. It was confirmed that the highest solar gain through exterior windows occurs in the warmer months. Lighting consumption varies between approximately 195 kWh and 220 kWh, with a more stable behavior during the middle months of the year. CO2 emissions followed the same behavior as lighting consumption since it was the only energized element in the bohio. This research demonstrated that passive strategies implemented in the vernacular dwelling work correctly, except for the minimum illuminance level, which needs to be improved.